Using Economic Evaluations to Inform Decision-Making in Oral Health: Transferability - Martorell-Guerra, B (Springer International Publishing, 2022)
In this chapter we review the concepts, tools, and methods available for transferability of economic evaluations published in one country or jurisdiction for use in another country or context. After reviewing the main conceptual considerations, academic development, and national guidelines on the subject, we use the example of one intervention aimed at the prevention of caries in children from the USA, to analyse its potential transferability to Chile – a South American country recently classified as high income by the World Bank. In doing this, we use a combination of tools to ensure the quality of the original study, adjustments for time and currency for a suitable comparison of results and costs, as well as applying the transferability analysis to the study, from its original country (i.e. USA) to Chile. The transferability analysis was performed using the general and specific criteria of Welte et al. as the main guiding tool but taking into consideration Chilean guidelines for cost-effectiveness analysis and local recommendations on transferability of economic evaluations. © Springer Nature Switzerland AG 2022.